Small molecule modulators of IL-17A/IL-17RA: a patent review (2013-2021) - Zhang, Bidong; Dömling, Alexander (Expert opinion on therapeutic patents, 2022)
INTRODUCTION: Interleukin-17A (IL-17A) is a well-established pro-inflammatory cytokine, which plays a pivotal role in immune and autoimmune diseases including psoriasis, asthma, psoriatic arthritis, and rheumatoid arthritis. Three currently approved monoclonal antibodies (mAbs) are in clinical practice for the treatment of multiple immune diseases. However, the disadvantages of the mAbs, such as non-oral administration, poor tissue penetration, lacking blood-brain barrier penetration, often long half-life times, narrow its application. Thus, intensive research is performed to discover potent small molecules, peptides, and macrocycles targeting the IL-17A/IL-17 RA protein-protein interaction (PPI) to modulate immune responses as an attractive approach for immunotherapy. AREAS COVERED: Small molecules, macrocycles, and peptides targeting IL-17A/IL-17RA PPI from 2013 to 2021. EXPERT OPINION: The rapid increase in the identification of small-molecule inhibitors of IL-17 should translate into a supplement of current biotherapeutics with mAbs. Potential advantages of small molecules over mAbs show room for clinical treatment improvement and new indication areas . An increasing number of patents and articles are recently published on small-molecule immunomodulators (SMIMs). Two compounds from Lilly and Leo Pharma are currently investigated in early clinical trials, followed by a Dice molecule. The outcome of these trials will influence future development of IL-17 inhibitors for treatment of inflammation-related diseases.
Keywords: Patents as Topic; Humans; patenty jako téma; Interleukin-17; interleukin-17; lidé